A new species of the Thelepus cincinnatus complex from Saint-Pierre and Miquelon Archipelago (NW Atlantic) and genetic diversity of Amphitrite figulus (Dalyell, 1853) (Annelida, Terebelliformia) - Lavesque, Nicolas; Pinsivy, Lucas; Daffe, Guillemine; Daramy, Flore; Grosse, Maël; Chauvaud, Laurent; Hutchings, Pat (Zootaxa, 2025)
During an ecological survey conducted in 2023 around the coastal waters of Saint-Pierre and Miquelon Archipelago, a sub-Arctic archipelago located about 20 km south of Newfoundland (NW Atlantic), two species of Terebelliformia were sampled. The first one is Amphitrite figulus (Dalyell, 1853) a species described from Europe but with a wide distribution across the Northern Atlantic Ocean. The second one, Thelepus recheri n. sp., is a new species characterised by the presence of a wide dorsal branchial gap and the presence of notopodia almost until the end of the body. Molecular studies were performed and two markers were sequenced and analyzed, COI and 16S. These genetic data revealed that (1) Thelepus recheri n. sp. belongs to the T. cincinnatus complex and (2) a clear population structure within A. figulus, with two populations on each side of the Atlantic separated from each other. However, our data are inconclusive in resolving whether these two clusters are two populations within the same species or two distinct species.